The Transformation of the Innovation Process: How Digital Tools are Changing Work, Collaboration, and Organizations in New Product Development*. Issue 1 (30th August 2020) - Marion, Tucker J.; Fixson, Sebastian K.
Abstract : Over the past several decades, digitization has invaded all areas of human activity, including innovation. The result of digitization of existing tools for design and collaboration, and the introduction of entirely new digital tools, is a far more substantive change of innovation than previous generations of tools enabled. It affects not only the quality of the output and speed of its generation, but it affects the innovation work itself, changes work content, collaboration patterns, decision authority, organizational set‐ups, governance structures, firm boundaries, and ultimately entire ecosystems. In this paper, the digitization of New Product Development (NPD), a subset of innovation, is studied to pursue two research questions: (1) How has the digital tool landscape in NPD changed over the past 15 years, and (2) how have these changes affected how firms innovate? This research uses a longitudinal multi‐method, qualitative approach to deep dive into actual use cases of digital design tools such as computer‐aided design CAD and new tools such as collaborative information technology (CIT). The changes in these tools and observations into how these tools are transforming the very nature of how things are designed is the research focus of this study. These tools have become increasingly more sophisticated while being easier to use and are integrated earlier in the design process. As a result, digital tools have a far broader reaching impact than previous generation of tools. Not only do they affect output and process efficiency, but they also increase depth and breadth of the work of individual innovators, they lead to rearrangement of the entire innovation processes, enable new configurations of people, teams, and firms, and rewrite the rules on how knowledge management acts as a critical competitive capability. The progression of digitization is laying the groundwork for changes to what firms are and do and points to different ways of organizing, specializing, and training for NPD professionals.